Application of silsesquioxanes for modification of epoxy resins - Heneczkowski, M.; Oleksy, M.; Oliwa, R.; Dutkiewicz, M.; Maciejewski, H.; Galina, H. (Polimery, 2013)
Composites consisting of low-molecular weight epoxy resin Epidian 6 and 0— 10 wt. % octakis[(3-glycidylpropyl)dimethylsiloxy]octasilsesquioxane (POSS_OG) cross-linked with triethylenetetramine (Z1) were prepared. The presence of POSS_OG in the composition improved its flow properties and reduced the heat evolved in exothermic cross-linking reaction. The resulting composites containing 1—6 wt. % POSS_OG had significantly increased (by 2—4 times) impact resistance and better flame resistance (increase of LOI by ~ 3.7 points) compared to the non-modified EP 6 resin. By using IR microspectroscopy mapping, an increase in the areas of the bands corresponding to O-Si-O groups was observed for the composites containing 1 wt. % silsesquioxane.